Use of compression therapy to treat lower limb wounds across Europe: a scoping review protocol - Ray Samuriwo; Alison Hopkins; Natalia Christiansen (BMJ Open)
Introduction Poor lower wound care is an avoidable patient harm. Compression therapy is an effective way of treating non-ischaemic lower limbs wounds, but it is not always used appropriately. There are many guidelines which set out how compression therapy should be used, but there is dearth of evidence about how it is actually used at a population level across Europe.Aim The aim of this scoping review is to map the evidence published in English relating to the use of compression therapy to treat lower limb wounds across Europe.Methods This scoping review will be conducted in line with the Joanna Briggs Institute and Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Protocols and Scoping Reviews guidance. A search for relevant publications will be conducted on variety of databases and key websites in order to identify a comprehensive range of relevant literature. Peer reviewed empirical papers, theoretical papers and other publications in English relating to the use of compression therapy across Europe will be considered for inclusion.Ethics and dissemination Ethical and research governance for this scoping review is not required because we will only gather secondary data. Our results will be disseminated to the widest possible audience through an open access paper in a peer reviewed international journal, conference presentations and a plain English summary. The results of this scoping review will be used by a panel of Key Opinion Leaders from across Europe to develop a driver diagram to underpin subsequent lower limb wound care improvement efforts.